Facile synthesized benzo[1, 2-b:4, 5-b']difuran based copolymer for both fullerene and non-fullerene organic solar cells. (20th May 2019) - Lei, Tao; Song, Wei; Fanady, Billy; Yan, Tingting; Wu, Lirong; Zhang, Wenxia; Xie, Lingchao; Hong, Ling; Ge, Ziyi
Abstract: A novel D-A conjugated polymer, PFBT-T, consisting of alkyl substituted benzo[1, 2-b:4, 5-b']difuran (BDF) as electron donor, alkyl substituted benzo[1, 2-c:4, 5-c']dithiophene-4, 8-dione (BDD) as electron acceptor and thiophene as the π-bridge has been designed and synthesized through facile Stille coupling reaction. Compared with its reported similar polymer based on benzo[1, 2-b:4, 5-b']thiophene (BDT) unit, PFBT-T has deeper LUMO and HOMO energy level and more intense absorption in 350–550 nm, leading to higher short-circuit current density ( J sc ) and open circuit voltages ( V oc ). Organic solar cells (OSCs) based on PFBT-T with architecture of ITO/PEDOT:PSS/PFBT-T:(PC71 BM or IT-M)/PDINO/Al were fabricated. OSCs using PC71 BM or IT-M as acceptors respectively obtained the power conversion efficiencies (PCEs) of 5.83% and 5.64%, which both were better than OSCs based on its BDT-based analogues. These results demonstrated that BDF was a promising donor constructing block which may replace BDT unit in some cases. Graphical abstract: New benzodifuran -based polymer PFBT-T was designed and synthesized, which was applied in both fullerene and non-fullerene organic solar cells. By blending polymer with IT-M, The optimal device performance exhibited a PCE of 5.64%, while in fullerene OSCs, optimal device performance exhibited a PCE of 5.83%.Image 1 Highlights: A facile way to synthesize benzo[1, 2-b:4, 5-b']difuran based copolymer with high yield. Systematic investigation of PFBT-T by CV, TGA, DSC, UV–vis spectra and so on. Synthesize benzo[1, 2-b:4, 5-b']difuran based copolymer achieved over 5.5% efficiency for both fullerene and non-fullerene solar cells.